KEPEMIMPINAN TRANSFORMASIONAL MEMODERASI PENGARUH SELF EFFICACY DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU SEKOLAH DASAR KECAMATAN PETUNGKRIYONO KABUPATEN PEKALONGAN (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze and test the Influence of Professional Competence and Discipline Work on the Performance of elementary school teachers throughout the District Tirto Pekalongan with Organizational Climate moderated.This type of research is a field research (field research), using a quantitative approach. The population in this study is a civil servant teachers in the district elementary Tirto Pekalongan regency totaling 213 teachers. Samples were taken using purposive technique of proportional random sampling, some 139 teachers. Techniques of analysis using multiple linear analysis testing, ² test, and hypothesis testing using t test. Based on the results of the study can be summarized as follows: professional competence has no effect on teacher performance, Work Discipline positive and significant impact on teacher performance, Climate Organizational positive and significant impact on teacher performance, Climate Organizational Professional Competence to strengthen the influence of teacher performance, and Organizational Climate Work Discipline strengthen the influence of the teachers' performance. Keywords : professional competence, discipline work, organizational climate, and teacher performance.